On the photomultiplier-tube asymmetry in TDCR systems. (September 2020) - Kossert, Karsten; Sabot, Benoît; Cassette, Philippe; Coulon, Romain; Liu, Haoran
Abstract: The responses of the three photomultiplier tubes (PMTs) in a triple-to-double coincidence ratio (TDCR) liquid scintillation (LS) system are often not identical. Such asymmetries can have a significant influence on activity determinations. The problem is often solved by means of a minimization algorithm which can easily be applied when analytical methods are used for the efficiency calculation, as is usually done for pure beta emitters. However, for radionuclides with more complex decay schemes, the counting efficiencies are often calculated with stochastic methods and the computation of the required corrections becomes very challenging. This paper presents a new numerical method to overcome the asymmetry problem for such complex decays and a comprehensive study on 55 Fe is described in detail. For the measurements, the asymmetry was varied by means of grey filter films which were placed in front of one of the photomultiplier tubes. In the case of the pure electron-capture (EC) radionuclide 55 Fe, the asymmetry can also be taken into account with a very simple correction which is derived assuming monoenergetic emissions. This work is also of great importance for the planned extension of the International Reference System (SIR) at the BIPM which will be used for international comparisons in radionuclide metrology. Highlights: PMT asymmetries in TDCR systems and related corrections are discussed. A new method based on a stochastic model is presented and applied to 55 Fe. A simple correction based on a monoenergetic assumption is presented. Experimental studies indicate that both corrections work well for 55 Fe. The monoenergetic approach is very useful as a comparison indicator for ESIR.